Proyecto para la evaluación socioeconómica de la ampliación y readecuación de la carretera progreso-playas a dos vías y cuatro carriles - Ramírez Contreras, Claudia Milagros (2010)
This study shows the feasibility analysis to run the investment project on the Provincial highway Playas - Progreo as the main route connecting between Playas, existing populations and the rest of the country. Its geographic location is part of one of the most important corridors of integration of the Ecuadorian coast, in addition to its regional importance, gives a national priority for this corridor as one of the largest flowing traffic on productive activities and tourist country. The people who benefit directly to the implementation of the project via Playas - Progreso are the road users without prejudice, 16 851 people between drivers and passengers of vehicles traveling on the road and all the people belonging to the centers villages; Progreso Parish, La Comuna San Antonio and Canton Playas. To improve the geometric characteristics of the track, better radios are generated, the less curvature of the road, visibility and under braking contingency Wider lanes, which will increase traffic flow capacity of the road, all of which, together with a plan maintenance, safe operating speeds result in higher, reduced operating costs by road users.